Wykorzystanie reguł dyskryminacyjnych do określania typu heteroskedastyczności w liniowym modelu ekonometrycznym - Grześkowiak, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This paper considers the utility of the application of discriminant functions to determine the best possible heteroscedasticity model of disturbances. Likelihood functions of certain models were pro-posed to determine the solution which was gained by conducting a comparison with the likelihood function of the vector Ɛ obtained with the usage of covariance matrix estimator suggested by Domowitz and White. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (19); 2007; nr 1180, s. 66-74